Anlotinib for the treatment of recurrent and refractory hemangioblastomas: a case report and review of literature - Tian, Qing; Zhou, Chaofeng; Zhou, Shifan; Wang, Sai; Feng, Baorong; Zhang, Keke; Zhang, Yu; Gao, Jieqiong; Mu, Xiaoyan; Guo, Zhizhong (Frontiers in Oncology, 2025)
Hemangioblastomas (HBs) are rare, highly vascular tumors that present significant treatment challenges, especially in cases of multiple recurrences. Here we present our experience treating one patient with recurrent and refractory HBs, aiming to provide preliminary data on the use of anlotinib in treating this disease. An 18-year-old woman with recurrent and refractory HBs, treated at the Henan Provincial Hospital of Traditional Chinese Medicine, achieved disease remission through oral anlotinib treatment after recurrence. After being diagnosed with HBs, the patient underwent multiple surgical treatments with some efficacy. After recurrence, additional surgery and radiotherapy were not feasible due to the presence of multiple tumor sites. Oral anlotinib (10mg, qd, q3w) resulted in disease remission and significantly improved the patient’s quality of life. Anlotinib may be employed in the management of recurrent and refractory HBs.